2010
DOI: 10.1002/jobm.200900378
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of docosahexaenoic acid by a low temperature‐adaptive strain Thraustochytriidae sp. Z105: screening and optimization

Abstract: As an alternative source in addition to fish oil, microbial production of docosahexaenoic acid has been recieved more and more attentions owing to their culture advantage. A unicellular eukaryotic microbe with high DHA production and capable of low temperature-adaptive growth was isolated from seawater and identified as Thraustochytriidae sp. Z105. The siginificant effect of temperature on cell growth and DHA synthesis by the strain was revealed. It could grow and produce DHA even at 4 degrees C, but hardly gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Heterotrophic cultivation without light, using inexpensive, well-defined mineral medium supplemented with a carbon source is feasible [46]. However, only a few species have been commercially explored and continuous efforts are made in order to diversify the range of microalgal species used [47]. This implies fermentation studies for growth medium optimization, and improvement of culture conditions and systems, in order to maximize the biosynthesis of n -3 LC-PUFA in each potential strain [48,49].…”
Section: Microalgae Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotrophic cultivation without light, using inexpensive, well-defined mineral medium supplemented with a carbon source is feasible [46]. However, only a few species have been commercially explored and continuous efforts are made in order to diversify the range of microalgal species used [47]. This implies fermentation studies for growth medium optimization, and improvement of culture conditions and systems, in order to maximize the biosynthesis of n -3 LC-PUFA in each potential strain [48,49].…”
Section: Microalgae Productionmentioning
confidence: 99%
“…The development of an efficient large-scale cultivation system for the commercial production of these nutrients from microalgae would address a major global need [7]. The market for these oils is at the moment limited by supply, hence isolation and exploitation of strains with important n -3 LC-PUFA production potential is on-going [47]. Since the microbial route of oil production through fermentation will always be more costly than potential agricultural alternatives ( i.e ., genetically modified crops), continuous efforts must be made in the sense of reducing production costs while focusing on high-value products with applications in human health [61].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…The negative effect of the too high concentration of glycerol on biomass could be attributed to the too high osmotic pressure imposed by glycerol, which has resulted in limited cell growth and product synthesis [ 23 ]. The effect of the initial amount of pure and raw glycerol on improving the production of DHA was investigated with a glycerol concentration ranging from 10 to 120 g/L (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the transformation of saturated fatty acids into unsaturated fatty acids occurred when oil-producing strains grow in oxygen-abundant environments [ 24 ]. The volume of the liquid medium was also noted that DO was affected, thus resulting in a lower DHA yield [ 25 ]. A large volume of liquid medium (more than 40 mL in a 250 mL flask) can also lead to a low DHA yield [ 16 ].…”
Section: Discussionmentioning
confidence: 99%